Paul W. Bruno, Kant’s Concept of Genius - Luciana M. Martínez (Mutatis Mutandis: Revista Internacional de Filosofía)
Reseña de Paul W. Bruno, Kant’s Concept of Genius. Its Origin and Function in the Third Critique, London-New York, Continuum International Publishing Group, 2010. 162 páginas. ISBN: 978-1-4411-3911-5.